Self-care in Patients with Heart Failure - Marques, Maria do Céu (2017)
Objectives: To adapt for the Portuguese language the Self-Care of Heart Failure Index V6.2, analyse the self-care in maintenance, management skills and self-confidence of patients with heart failure who attend the nursing consultation of two Hospitals. Method: Explo- ratory study, sample 110 patients who frequented the nursing consultation for patients with heart failure of two Portuguese hospitals, conducted in the period of 6 months. He appea- led to the descriptive statistics and psychometric tests. Results: Internal consistency similar to the original scale. Mostly elderly, low literacy patients in self-care, low values associated with physical activity to the control of salt in meals taken away from home and inadequate control of signs and symptoms. Conclusion: Patients’ present difficulties in maintenance and management of the disease are self-confident face anyway. This instrument allows for individualized assessment leading to decision-making and action adjusted.